Economic and Politico-Economic Equivalence - Martín Gonzalez-Eiras; Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2012)
We extend "economic equivalence" results, like the Ricardian equivalence proposition, to the political sphere where policy is chosen sequentially. We derive conditions under which a policy regime (summarizing admissible policy choices in every period) and a state are "politico-economically equivalent" to another such pair, in the sense that both pairs give rise to the same equilibrium allocation. We apply the conditions in the context of politico-economic theories of government debt as a means to i) deliver intergenerational transfers or ii) smooth tax distortions. We find that certain politico-economic models of social security or variants thereof can be re-interpreted as novel politico-economic theories of debt while other models cannot, possibly explaining the political conflict surrounding social security reform. We also find that in environments with distorting taxes, economic equivalence relations between policies with different levels of debt do not extend to the political sphere.
Keywords: E62; H55; H63; 330; Equivalence; social security; government debt; social security reform; Finanzpolitik; Öffentliche Schulden; Neue politische Ökonomie; Ricardianische Äquivalenz; Soziale Sicherheit; Sozialreform; Theorie